2018
DOI: 10.1111/jdv.15052
|View full text |Cite
|
Sign up to set email alerts
|

Different outdoor professions have different risks – a cross‐sectional study comparing non‐melanoma skin cancer risk among farmers, gardeners and mountain guides

Abstract: Different outdoor professions have significant different risks for NMSC and show different risk behaviour. Tailoring prevention efforts to different professions based on their individual needs could be the key to lower the global burden of (occupational) NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
1
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 41 publications
3
44
1
12
Order By: Relevance
“…However, the vast majority of farmers are self‐employed and therefore these regulations do not apply. At the same time, several previous studies have shown that among the outdoor professions farmers have one of the highest rates of KC, with poor primary prevention measures taken during work hours . In Bavaria, only a small minority of farmers regularly use sunscreen, wide‐brimmed hats, sunglasses, long‐sleeved clothing or other UVR‐protective measures .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the vast majority of farmers are self‐employed and therefore these regulations do not apply. At the same time, several previous studies have shown that among the outdoor professions farmers have one of the highest rates of KC, with poor primary prevention measures taken during work hours . In Bavaria, only a small minority of farmers regularly use sunscreen, wide‐brimmed hats, sunglasses, long‐sleeved clothing or other UVR‐protective measures .…”
mentioning
confidence: 99%
“…1,[15][16][17] Outdoor workers and, in particular, farmers, typically exposed to UVR during their daily work, for up to 40 hours per week, 18 are at a substantially higher risk of KC than indoor workers. [19][20][21] This has led to the recognition of KC as an occupational disease of outdoor workers in several countries worldwide, including Germany. [22][23][24] In Germany, about 2-3 million individuals are categorized as 'outdoor workers', including, for example, farmers, construction workers, gardeners and roofers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, lifetime occupational exposure was definitely positively associated with SCC, especially when the latest diagnostic methods were used. Outdoor workers show high risk of skin cancer, and that risk differs by outdoor activity . To summarize, there is a clear association between NMSC (both BCC and SCC) and UV exposure.…”
Section: Discussionmentioning
confidence: 96%
“…However, studies conducted in Bavaria, Germany – a region with many rural farms – have shown that risk awareness is low and actual sun‐protective behaviours (such as the regular use of sunscreen, wearing long‐sleeved shirts and wide‐brimmed hats) are poor . What remains unknown is why these behaviours are not implemented.…”
mentioning
confidence: 99%